2011
DOI: 10.1007/bf03393095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conditioning Voices as Reinforcers for Listener Responses on Rate of Learning, Awareness, and Preferences for Listening to Stories in Preschoolers With Autism

Abstract: We used a delayed non-concurrent pre- and post-intervention probe design to test the effects of a voice conditioning protocol (VCP) with 3 preschoolers with autism on (a) rate of acquisition of listener curricular objectives, (b) observing voices and the presence of adults across 3 settings, (c) selecting to listen to adults tell stories in free play setting, and (d) the occurrence of stereotypy in the story setting. The VCP conditioned voices as reinforcers for listening to recordings of voices via stimulus-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 43 publications
2
29
0
5
Order By: Relevance
“…The child must both listen to the voice and look at the visual stimulus (or contact other sensory stimuli), and reinforcement for one or both observing responses may need to be present for echoic behavior to join listener and speaker repertoires. Dinsmoor (1983), Greer and Han (2014), and Greer et al (2011b) demonstrated that observing responses could be conditioned and that doing so increased rates of learning of related discriminations. Most notably, after 2-dimensional visual stimuli and the observing response of looking at 2-dimensional stimuli were conditioned as reinforcers, participants acquired generalized visual identity-matching repertoires and increased correct responding across listener responses (Greer and Han 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The child must both listen to the voice and look at the visual stimulus (or contact other sensory stimuli), and reinforcement for one or both observing responses may need to be present for echoic behavior to join listener and speaker repertoires. Dinsmoor (1983), Greer and Han (2014), and Greer et al (2011b) demonstrated that observing responses could be conditioned and that doing so increased rates of learning of related discriminations. Most notably, after 2-dimensional visual stimuli and the observing response of looking at 2-dimensional stimuli were conditioned as reinforcers, participants acquired generalized visual identity-matching repertoires and increased correct responding across listener responses (Greer and Han 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Greer, Pistoljevic, Cahill, and Du () evaluated the effects of RCP to establish the speech of others as a conditioned reinforcer for three children with ASD. The RCP condition consisted of allowing the child to press a button under a free‐operant arrangement.…”
mentioning
confidence: 99%
“…No entanto, com o decorrer da implementação, a cuidadora relatou para a experimentadora que o participante emitia as relações intraverbais (ex., "machado em inglês é ax") fora do ambiente experimental. Com base nessa informação e no conhecimento sobre a função discriminativa/reforçadora que a mãe/cuidadora exerce desde cedo no desenvolvimento infantil (Greer, Pistoljevic, Cahill, & Du, 2011;Longano & Greer, 2015;Petursdottir & Lepper, 2015;Petursdottir, Carp, Matthies, & Esch, 2011), uma vez finalizada a implementação dos 51 ciclos previstos para os casos nos quais os participantes não alcançassem o critério de aprendizagem, foi realizada uma sessão de teste de intraverbal aplicado pela cuidadora no ambiente experimental (sob supervisão da experimentadora) 6 . Neste teste (teste (mãe) na Figura 2), P1 apresentou 100% de respostas intraverbais corretas nas relações de ambos os tratamentos.…”
Section: Concordância Entre Observadores E Integridade Do Procedimentounclassified